PENINGKATAN KREATIVITAS KELOMPOK PEREMPUAN DI MASA PANDEMI COVID-19 MELALUI MODERNISASI PENGOLAHAN PANGAN LOKAL DI WILAYAH PERBATASAN, KALIMANTAN TIMUR - Miftakhur Rohmah; Anton Rahmadi; Uni W Sagena (Universitas Trisakti, 2021)
The aim of this community service is to increase the community's women creativity PKK group in Talisayan District Berau, East Kalimantan driven in processing local food resources, fisheries and agriculture. However, so far the produce is only sold in fresh form in simple and traditional way so that during this pandemic period this activity has been hampered. Solutive efforts are being made to increase creativity and optimize abundant food products of fish and corn through modernization of technology and processing methods so that they can be marketed outside the region in order to increase community income. The community service method carried out is in the form of training and mentoring for PKK groups to be more creative, innovative, and skilled in processing food safely and attractively so that it has a high selling value. Safe, secure, and attractive food processing can increase product durability, maintain its nutritional content, safe for consumer health, and can boost marketing, even have the potential to export abroad. The resulting output is the application of technology and increasing the quality, quantity and added value of processed food products thanks to the creativity and skills of the community in processing local food of Talisayan. Another output is the establishment of centers for food processing quality driven by women in PKK groups. This is where the role of academics and partners in the local community is needed to work together as a concern and service for the sake of increasing income of the community.